Psychosocial Stressors in Relation to Unsafe Acts - Javaid, Muhammad Umair; Isha, Ahmad Shahrul Nizam; Ghazali, Zulkipli; Langove, Naseebullah (International Review of Management and Marketing, 2016)
The psychosocial stressor has become a prevailing phenomenon around the globe and is the major factor contributing towards the poor health and unsafe acts (leads to accidents) of the workers. These stressors at plant turnaround maintenance process are the most neglected context in petrochemical industries of Malaysia. The use of biomarkers in this study will be helpful to look into the actual health status of the workers due to psychosocial and work-related risks. The result of previous studies are contradicting and does not give a clear picture, therefore this study will particularly look into the relationship of demographic characteristics and working hours on psychosocial stress and their impact on unsafe acts. There are so many reasons that lead to accidents, but understanding the underlying reasons of these unsafe acts from the psychosocial perspective is very crucial. Keywords: Accidents, Psychosocial stressors, Petrochemical industry, Unsafe act JEL Classification: M3